Alterações antropogênicas e seu efeito sobre a comunidade de heteroptera (gerromorpha) - Silva, Karina Dias da (2015)
There are large gaps in knowledge about the identity of species 21 (Linnean shortfall) and their spatial distribution (Wallacean shortfall). These gaps are 22 especially of particular concern in least developed countries in tropical regions which 23 harbor great species diversity but still lack of investments in conservation. In addition, 24 these regions are important areas for agricultural production, making the ignorance even 25 more worrying for conservation. Our objective was to analyze the temporal dynamics of 26 scientific literature on aquatic and semiaquatic Heteroptera, adressing questions related 27 to gaps of knowledge in this taxonomic group in Brazil and South America. Researches 28 focused on Heteroptera have been advancing in the last years, but much remains to 29 bedone. Especially for countries like Brazil, which lacks of satisfactory knowledge 30 about its fauna and its spatial/environmental relationships, especially in difficult access 31 areas and also in areas that have little or no one qualified researcher.